Implementation of Road Infrastructure Development by the Village Government as an Effort to Improve Community Social Accessibility in Nagauleng Village, Cenrana District, Bone Regency - Jumiati; Hikmah, Nurul; Syafaririn, Rahma Aulia; Reski, Sulfa; Sadriani, Andi (Formosa Journal of Applied Sciences, 2024)
Village government is expected to have an impact on improving the welfare of local village communities through the development of road infrastructure. This research aims to determine the role of the village government in developing road infrastructure in Nagauleng Village, Cenrana District, Bone Regency and to determine the facilitators and inhibitors of infrastructure development activities. Data analysis using an internal analysis model shows that the role of the village government in the development of Nagauleng village road infrastructure is still lacking and not optimal, this is due to a lack of planning, implementation and other supporting factors. On the other hand, inhibiting factors include a lack of oversight and monitoring of infrastructure development, a lack of budget from the government as well as difficult access and terrain where the location is a main road, thus complicating the infrastructure development process which takes a lot of time.